2001
DOI: 10.1046/j.1365-3180.2001.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological evidence for a 1:1 Ca2+:glyphosate association in deposit residuals on the leaf surface of barley

Abstract: It has long been known that calcium ion antagonizes glyphosate, but it was not clear whether the stoichiometry of their interaction is 1:1 or 1:2. Two independent methods were used to determine which stoichiometry was the most probable. First, dose±response curves of barley (Hordeum vulgare L.) plants treated with glyphosate were determined in the presence of 0, 1.25, 2.5, 5 and 10 mM CaCl 2 . The doses of`free' glyphosate (not inactivated by calcium ion) were computed using the assumptions of 1:1 and 1:2 stoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
2
8
2
Order By: Relevance
“…3). At doses ranging from 67.5 to 1080 g ha −1 , maximum uptake reached nearly 100% of the applied label, and t 1/2 was in the range 2.3–3 h. Contrary to previous experiments (Gauvrit et al. , 2001) with barley ( Hordeum vulgare L.), no lag time was observed before the onset of glyphosate uptake.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…3). At doses ranging from 67.5 to 1080 g ha −1 , maximum uptake reached nearly 100% of the applied label, and t 1/2 was in the range 2.3–3 h. Contrary to previous experiments (Gauvrit et al. , 2001) with barley ( Hordeum vulgare L.), no lag time was observed before the onset of glyphosate uptake.…”
Section: Resultscontrasting
confidence: 72%
“…For example, uptake into Apocynum cannabinum L. was 19%, 36% and 53% of the applied label after 12, 72 and 288 h respectively (Schultz & Burnside, 1980). In a previous study on barley, we found t 1/2 values to be around 30 h (Gauvrit et al. , 2001), when compared with 2–3 h in this study.…”
Section: Discussionsupporting
confidence: 63%
“…Obviously, on the highly weathered Arenosol with low buffering capacity, glyphosate was sufficiently available in the soil solution for interactions with the roots of sunflower as a non-target plant. High Ca 2+ concentrations in the calcareous sub-soil (30% CaCO 3 ) may lead to rapid complexation and immobilization of glyphosate (Gauvrit et al 2001;Schönherr and Schreiber 2004) to make it unavailable for plant roots and to protect it from conversion to AMPA, which can exert phyto- 132.5a (±33.5)…”
Section: Plant Growthmentioning
confidence: 99%
“…This complex or salt is poorly absorbed by plants (Nilsson 1985); in addition, suggested that glyphosate is entrapped in a solid residue on the leaf surface. The stoichiometry of the glyphosatecalcium association was shown to be 1:1 (de Ruiter et al 2002;Gauvrit et al 2000Gauvrit et al , 2001, as suggested by Nalewaja et al (1996). Under conditions in France calcium concentration is rarely higher than 5 mM (Blondlot et al 1999).…”
Section: Introductionmentioning
confidence: 88%
“…It was confirmed that the chloroform wash recovered more than 96% of nonpenetrated 14 C-glyphosate, although glyphosate and its calcium salts or chelate are not soluble in chloroform (Franz et al 1997). Presumably, the chloroform dissolved the wax on which 14 C-glyphosate and its salts or chelate were present (Gauvrit et al 2001). To 75a D and C denote the upper and lower limits of dry matter at zero and at very large doses of glyphosate; ED 50 and ED 90 denote the doses of glyphosate required to reduce dry matter by 50 and 90%, respectively, between the upper and lower limits; and b is proportional to the slope of the curve around ED 50 .…”
Section: Methodsmentioning
confidence: 99%